Effects of Chitosan Membrane on Osteogenesis and Oral Wound Healing: A Literature Review - Ni Putu Dian Cipta Dewi; Ni Putu Sulistiawati Dewi (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Chitosan is a compound produced from processed shrimp shell waste that has an important role in the medical industry. Chitosan is a straight-chain amino polysaccharide compound consisting of glucosamine monomers (poly-1,4-D- glucosamine) linked through (1-4) β-glycosidic bonds, derived from deacetylated chitin. In dentistry, chitosan plays an important role in wound healing and bone formation (osteogenesis). Review: This literature aims to further explain the effectiveness of chitosan membranes in bone formation and wound healing in the oral cavity. Osteoblasts are new bone-forming cells, including the process of breaking down old bone and replacing it with new, healthier bone. Chitosan membranes can reduce osteoclast activity and prevent further bone resorption. Chitosan membrane plays a role in reducing the production of prostaglandin E2 and inflammatory cytokines namely Interleukin-1, Interleukin-6, and Tumor Necrosis Factor-α which play a role in the differentiation and activation of osteoclast cells directly through the activator of kβ ligand receptors. The wound healing process is dynamic and complex through systematic steps such as hemostatic, inflammatory, proliferative, and regenerative phases. Many studies have shown that chitosan membranes can accelerate wound healing by increasing the productivity of inflammatory cells. Conclusion: Chitosan membrane is very effective in promoting osteoclastogenesis, because it can stimulate macrophage cells to reduce the production of prostaglandin E2 (PGE2) mediators, resulting in osteoclast cellular activity can be inhibited and osteoblast formation can be increased. Chitosan membrane plays an important role in accelerating wound healing by increasing the production of inflammatory mediators such as macrophages, fibroblasts, polymorphonuclear leukocytes (PMN), and osteoblasts.